Various Sources of Financing for Advanced Businesses Including Bank Loans, Angel Investments, and Crowdfunding - Mulyani, Nurasri; Nurhayat, Nurhayat; Kamarudin, Syamsu A (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Financing is one of the key factors in business development, especially in the advanced phase after the business has successfully passed the initial stage. In this stage, entrepreneurs are faced with various choices of financing sources to support business expansion, product innovation, and increase competitiveness. This research uses a qualitative descriptive method which uses an approach to study literature. This research aims to determine various sources of financing for advanced businesses, including bank loans, angel investment and crowdfunding and the challenges of each source of financing based on existing literature. By understanding the characteristics of each source of financing, entrepreneurs can make more informed decisions in choosing financing alternatives that best suit their business needs.